Electric, Dielectric, and Dynamic Mechanical Behavior of Carbon Black/Styrene-Butadiene-Styrene Composites - LEYVA, M.E.; BARRA, M.M.O.; MOREIRA, A.C.F.; SOARES, B.G.; KHASTGIR, D.
The conductivity of styrene-butadiene-styrene block copolymers containing different amounts of extraconductive carbon black (CB)was investigated as a function of the mold temperature. The composites exhibited reduced percolation thresholds (between 1.0 and 2.0 vol
Keywords: STYRENE-BUTADIENE-STYRENE (SBS)/CARBON BLACK COMPOSITES; DYNAMIC MECHANICAL ANALYSIS; DIELECTRIC RELAXATION; CONDUCTIVITY; DIELECTRIC PROPERTIES; RELAXATION; BLOCK COPOLYMER